Emulsion-templated microparticles with tunable stiffness and topology: Applications as edible microcarriers for cultured meat. (August 2022) - Norris, Sam C.P.; Kawecki, N. Stephanie; Davis, Ashton R.; Chen, Kathleen K.; Rowat, Amy C.
Abstract: Cultured meat has potential to diversify methods for protein production, but innovations in production efficiency will be required to make cultured meat a feasible protein alternative. Microcarriers provide a strategy to culture sufficient volumes of adherent cells in a bioreactor that are required for meat products. However, cell culture on inedible microcarriers involves extra downstream processing to dissociate cells prior to consumption. Here, we present edible microcarriers that can support the expansion and differentiation of myogenic cells in a single bioreactor system. To fabricate edible microcarriers with a scalable process, we used water-in-oil emulsions as templates for gelatin microparticles. We also developed a novel embossing technique to imprint edible microcarriers with grooved topology in order to test if microcarriers with striated surface texture can promote myoblast proliferation and differentiation in suspension culture. In this proof-of-concept demonstration, we showed that edible microcarriers with both smooth and grooved surface topologies supported the proliferation and differentiation of mouse myogenic C2C12 cells in a suspension culture. The grooved edible microcarriers showed a modest increase in the proliferation and alignment of myogenic cells compared to cells cultured on smooth, spherical microcarriers. During the expansion phase, we also observed the formation of cell-microcarrier aggregates or 'microtissues' for cells cultured on both smooth and grooved microcarriers. Myogenic microtissues cultured with smooth and grooved microcarriers showed similar characteristics in terms of myotube length, myotube volume fraction, and expression of myogenic markers. To establish feasibility of edible microcarriers for cultured meat, we showed that edible microcarriers supported the production of myogenic microtissue from C2C12 or bovine satellite muscle cells, which we harvested by centrifugation into a cookable meat patty that maintained its shape and exhibited browning during cooking. These findings demonstrate the potential of edible microcarriers for the scalable production of cultured meat in a single bioreactor. Graphical abstract: Image 1